Distributional shifts of canopy‑forming seaweeds from the Atlantic coast of Southern Europe - Casado-Amenzúa, Pilar; Araújo, Rita; Bárbara, Ignacio; Bermejo-Lacida, Ricardo; Borja, Ángel; Díez, Isabel; Fernández, Conxi; Gorostiaga, José M; Guinda, Xavier; Hernández, Ignacio; Juanes, JA; Peña, Viviana; et al. (Springer, 2019)
Canopy-forming seaweeds sustain critical ecosystem services in coastal habitats. Around the world, many of these seaweeds are suffering strong declines, mainly attributed to the progressive increase in sea surface temperature, in combination with other stressors due to current global changes. The southernmost part of the NE Atlantic is among those areas most affected by climate change. In this study, we estimated the distributional contractions of seven of the most conspicuous seaweeds from the Atlantic coasts of the Iberian Peninsula using an “Extent of Occurrence” methodology. Overall, during the last three decades, range shifts have been more pronounced east of the Cantabrian Sea than along the western coast of the Iberian Peninsula. In particular, regions with a semi-permanent summer upwelling seem to be critical to the persistence of brown seaweeds, fucoids and kelps. Range contractions of the cold-temperate fucoids were estimated to be ca. 21% and 45% for Himanthalia elongata and Fucus serratus, respectively; and for the kelps Saccharina latissima and Laminaria hyperborea, 6% and 14%, respectively. Range contractions for warmtemperate kelps were estimated to be ca. 13% and 10% for Saccorhiza polyschides and L. ochroleuca, respectively. Finally, a decline in the warm-temperate red algae Gelidium corneum occurred only in the easternmost area of the Cantabrian Sea (Basque Country), leading to a distributional contraction of 7%. We recommend conservation actions to better manage the remnant populations of these canopy-forming seaweeds, and their inclusion in national and regional catalogues of endangered species and on international Red Lists.
Keywords: Algas - Atlántico (Costa, España); Kelp forests; Fucoids; Red algae; Climate change; Range contraction; Community replacement